A new criterion of coal burst proneness based on the residual elastic energy index - Gong, Fengqiang; Wang, Yunliang; Wang, Zhiguo; Pan, Junfeng; Luo, Song (International journal of mining science and technology, 2021)
To evaluate the coal burst proneness more precisely, a new energy criterion namely the residual elastic energy index was proposed. This study begins by performing the single-cyclic loading-unloading uniaxial compression tests with five pre-peak unloading stress levels to explore the energy storage characteristics of coal. Five types of coals from different mines were tested, and the instantaneous destruction process of the coal specimens under compression loading was recorded using a high speed camera. The results showed a linear relationship between the elastic strain energy density and input energy density, which confirms the linear energy storage law of coal. Based on this linear energy storage law, the peak elastic strain energy density of each coal specimen was obtained precisely. Subsequently, a new energy criterion of coal burst proneness was established, which was called the residual elastic energy index (defined as the difference between the peak elastic strain energy density and post peak failure energy density). Considering the destruction process and actual failure characteristics of coal specimens, the accuracy of evaluating coal burst proneness based on the residual elastic energy index was examined. The results indicated that the residual elastic energy index enables reliable and precise evaluations of the coal burst proneness.